Hybrid Low‐Dimensional Carbon Allotropes Formed in Gas Phase. (13th September 2020) - Ahmad, Saeed; Mustonen, Kimmo; McLean, Ben; Jiang, Hua; Zhang, Qiang; Hussain, Aqeel; Khan, Abu Taher; Ding, Er‐Xiong; Liao, Yongping; Wei, Nan; Monazam, Mohammad R. A.; Nasibulin, Albert G.; et al.
Abstract: Graphene, carbon nanotubes (CNTs) and fullerenes are the basic set of low‐dimensional carbon allotropes. The latter two arise from the former by selective removal and addition of carbon atoms. Nevertheless, given their morphological disparities, the production of each is typically devised from entirely different starting points. Here, it is demonstrated that all three allotropes can nucleate from (pseudo‐)spherical, nanometer‐sized transition metal clusters in a gas‐suspension when the chemical conditions are favorable. The experimental results indicate that graphitic carbon embryos nucleate on the catalyst particles and sometimes transform into 2D graphene flakes through chain polymerization of carbon fragments forming in the surround gas atmosphere. It is further shown that hydrogenation reactions play an essential role by stabilizing the emerging flakes by mitigating the pentagon and heptagon defects that lead into evolution of fulleroids. Ab initio molecular dynamics simulations show that the ratio of hydrogen to carbon in the reaction is a key growth parameter. Since structural formation takes place in a gas‐suspension, graphene accompanied by fullerenes and single‐walled CNTs can be deposited on any surface at ambient temperature with arbitrary layer thicknesses. This provides a direct route for the production and deposition of graphene‐based hybrid thin films for various applications. Abstract : Graphene, single‐walled carbon nanotubes and fullerenes form the basic set of low‐dimensional carbon allotropes. Nevertheless, given their morphological disparities, the production of each is typically devised from entirely different starting points. Here, it is demonstrated that all three allotropes can nucleate from nanometer‐sized transition metal particles in a gas‐suspension when the chemical conditions are favorable.